Monoclonal antibodies to host cellular receptors for the treatment and prevention of HIV-1 infection. Issue 3 (May 2015) - Pace, Craig; Markowitz, Martin
Abstract : Purpose of review: Clinically relevant monoclonal antibodies (mAb) to host cellular receptors have been generated to both the CD4 receptor and the CCR5 coreceptor, cell surface proteins critical for HIV-1 entry. Ibalizumab is a novel humanized mAb that binds to a conformational epitope on CD4 and blocks entry of HIV-1. It has broad and potent antiviral activity in vitro and in vivo . PRO 140 is a humanized mAb that binds to the CCR5 coreceptor and inhibits CCR5-tropic HIV-1 by interfering with viral entry. Antiviral activity has been demonstrated both in vitro against R5 viruses and in vivo in HIV-1-infected individuals harboring CCR5-tropic virus. Recent findings: Both antibodies have been administered intravenously in early-phase clinical trials, and current emphasis is on the development of formulations that can be administered subcutaneously. Most recently, bispecific antibodies combining either ibalizumab or PRO 140 with anti-Env broadly neutralizing antibodies have been constructed with vastly improved in-vitro neutralizing profiles, and may offer substantial advantages in the clinic. Summary: mAb to host cellular receptors particularly when combined with broadly neutralizing antibodies in novel conformations may offer advances in both the treatment and prevention of HIV-1 infection.